Human IL-2Rɑ subunit binding modulation of IL-2 through a decline in electrostatic interactions: A computational and experimental approach - Beig Parikhani, Arezoo; Bagherzadeh, Kowsar; Dehghan, Rada; Biglari, Alireza; Shokrgozar, Mohammad Ali; Riazi Rad, Farhad; Zeinali, Sirous; Talebkhan, Yeganeh; Ajdary, Soheila; Ahangari Cohan, Reza; Behdani, Mahdi (PloS one, 2022)
Although high-dose IL-2 has clear antitumor effects, severe side effects like severe toxicity and activation of Tregs by binding of IL-2 to high-affinity IL-2R, hypotension, and vascular leak syndrome limit its applications as a therapeutic antitumor agent. Here in this study, a rational computational approach was employed to develop and design novel triple-mutant IL-2 variants with the aim of improving IL-2-based immunotherapy. The affinity of the mutants towards IL-2Rα was further computed with the aid of molecular dynamic simulations and umbrella sampling techniques and the obtained results were compared to those of wild-type IL-2. In vitro experiments by flow cytometry showed that the anti-CD25 mAb was able to bind to PBMC cells even after mutant 2 preincubation, however, the binding strength of the mutant to α-subunit was less than of wtIL-2. Additionally, reduction of IL-2Rα subunit affinity did not significantly disturb IL-2/IL2Rβγc subunits interactions.